Improving the working performance of automatic ball balancer by modifying its mechanism. (8th December 2015) - Rezaee, Mousa; Fathi, Reza
Abstract: An automatic ball balancer consists of several balls that are free to move in the circular race containing a damping fluid. Although a traditional ABB can improve the vibration behavior of an unbalanced rotor under proper working conditions, at speeds below the first critical speed, it makes the vibration amplitude of the rotor larger than that of a rotor without an automatic ball balancer. Moreover, it has a limited stable region of the perfect balancing configuration. Considering these deficiencies, in this study a new design for automatic ball balancer is proposed. To analyze the problem, the nonlinear governing equations of a rotor equipped with the new ABB are derived using Lagrange׳s equations. Then, stability analysis is carried out on the basis of linearized equations of motion around the equilibrium positions to obtain the stable region of the system. It is shown that the new ABB can prevent the rotor from increasing the vibrations at the transient state. Also, it increases the stable region of the perfect balancing configuration. Comparing the results with those corresponding to the traditional ball balancer shows that the new ABB can reduce the vibration amplitude at speeds below the first critical speed and it increases the stable region of the perfect balancing configuration.